Dinamika Pemilihan Umum Kepala Daerah Kalimantan Timur - Sudiran, Florentinus (Universitas 17 Agustus 1945 Samarinda, 2016)
The aim of this research is to know the general election ofÂ the mayor of Samarinda city in 2014.The location of it is in Samarinda.The research had been carried out in the year.The method of it is a discriptive kualitative and library one.The data is taken from the daily newspaper here.The result of it is that the general election mentioned aboveÂ (1).It had been running well, (2).It was still any handicap, (3).The former mayor and regents (incombent/petahana) got the winners:among are Saharie Jaang in Samarinda city,Razal Effendi in Balikpapan city and Rita Widyasari in Tenggarong Regency.The new comers among are are Ismunandar from East Kutai regency, Geh from Mahulu, from West Kutai,Muharam From Berau,Mardikansyah from Paser,Neny from Bontang city, (4).Some are not fair play especially done by the succes-team (5).The former (incombent/petahana) got the majority. The suggestions are (1).The socialization of the election concerned has to prepare perfectly,(2).The execution of the election has to be direct, general, free, honest, justice and secret, (3).The supremacy of law concerned has to be taken seriously.